A construção de um relacionamento na perspectiva do poliamor - Reis, Janaina Batista Gonzalez (2017)
This is a qualitative research with a case study designed on polyamory. Polyamory emerged in the 1990s as a new mode of loving relationship, a paradigmatic representation of contemporary love. Unrelated to a particular sexual identity, as a specific modality of non-monogamy, being a relationship orientation in which is believed the possibility and acceptance to love many people, maintaining multiple intimate relationships. This family arrangement is already present in many countries and in Brazil the latest survey in a social media group indicated 17,487 members interested in the topic. The instrument used was the semi-structured interview and narratives obtained, classified in three categories: Experiencing the quotidian, Experiencing the social, and Constructing gender relationships in the polyamory. The results showed some similarities with other conventional family arrangements such as: division of tasks, jealousy, hierarchy, gender issues and others. Conjugality and sexuality are peculiar to the researched family and follow established criteria in polyamorous arrangements. We suggest further studies on polyamorous families in our reality